A GWAS approach to find SNPs associated with salt removal in rice leaf sheath - Neang, Sarin; de Ocampo, Marjorie; Egdane, James A.; Platten, John Damien; Ismail, Abdelbagi M.; Seki, Masahide; Suzuki, Yutaka; Skoulding, Nicola Stephanie; Kano-Nakata, Mana; Yamauchi, Akira; Mitsuya, Shiro (Oxford University Press, 2020)
and AimsThe ability for salt removal at the leaf sheath level is considered to be one of the major mechanisms associated with salt tolerance in rice. Thus, understanding the genetic control of the salt removal capacity in leaf sheaths will help improve the molecular breeding of salt-tolerant rice varieties and speed up future varietal development to increase productivity in salt-affected areas. We report a genome-wide association study (GWAS) conducted to find single nucleotide polymorphisms (SNPs) associated with salt removal in leaf sheaths of rice.MethodsIn this study, 296 accessions of a rice (Oryza sativa) diversity panel were used to identify salt removal-related traits and conduct GWAS using 36 901 SNPs. The sheath:blade ratio of Na+ and Cl– concentrations was used to determine the salt removal ability in leaf sheaths. Candidate genes were further narrowed via Gene Ontology and RNA-seq analysis to those whose putative function was likely to be associated with salt transport and were up-regulated in response to salt stress.Key resultsFor the association signals of the Na+ sheath:blade ratio, significant SNPs were found only in the indica sub-population on chromosome 5. Within candidate genes found in the GWAS study, five genes were upregulated and eight genes were downregulated in the internal leaf sheath tissues in the presence of salt stress.ConclusionsThese GWAS data imply that rice accessions in the indica variety group are the main source of genes and alleles associated with Na+ removal in leaf sheaths of rice under salt stress.